Enriching Sami language distance education - Helander, Hanna; Pieski, Satu-Marjut; Keskitalo, Pigga (Routledge, 2023)
In this chapter, a pedagogical innovation study on playful learning is presented in the context of Sami language distance education in Finland. Given the varied effects of deep-rooted coloniality, especially regarding how people think and act, it is important to rethink pedagogical arrangements when educating current and future Indigenous children and youth. The model developed during this research project displays the key elements of traditional knowledge transformation and Sami language education in distance-learning environments. The pedagogical challenges faced by Sami education within Indigenous education fields are highlighted. Our research indicates that joint innovation studies based on teacher expertise is a key element in changing teaching practices and educational contexts. Research that aims to emancipate children’s agency is vital, and it is important to develop learning arenas that will position the well-being and interests of children at the centre.